Bridging research and good practices towards patients welfare : proceedings of the 4th International Conference on Healthcare Ergonomics and Patient Safety (HEPS), Taipei, Taiwan, 23-26 June 2014 /: proceedings of the 4th International Conference on Healthcare Ergonomics and Patient Safety (HEPS), Taipei, Taiwan, 23-26 June 2014. (2014) - Unknown
No abstract available